Helicobacter pylori infection & immune thrombocytopenic purpura in children and adolescents: A randomized controlled trial. (June 2015) - Brito, Helena Shino Hanai; Braga, Josefina Aparecida Pellegrini; Loggetto, Sandra Regina; Machado, Rodrigo Strehl; Granato, Celso Francisco Hernandes; Kawakami, Elisabete
Abstract Helicobacter pylori and immune thrombocytopenic purpura (ITP) association is not well established in chronic ITP (cITP) in children, although the cure of thrombocytopenia in approximately half of H. pylori eradicated adult patients has been described. The aim of this study was to investigate the effect of H. pylori eradication on platelet (PLT) recovery in cITP children and adolescents through a randomized, controlled trial. A total of 85 children (mean age 11.4 years) with cITP were prospectively enrolled. Diagnosis of H. pylori was established by two locally validated tests, 13C-urea breath test and monoclonal stool antigen test. Twenty-two infected patients were identified, and randomly allocated into two groups: H. pylori treatment group (n = 11) and the non-intervention control group (n = 11). The control group was offered treatment if the thrombocytopenia persisted after the follow-up. At baseline, there were no differences regarding age, sex, duration of disease, and PLT count between groups. Sixty three of 85 patients were uninfected. PLT response was classified as complete response: PLT > 150 × 109 l−1; partial response: PLT 50–150 × 109 l−1, or an increase of 20–30 × 109 l−1; no response: PLT < 50 × 109 l−1 or an increase of <20 × 109 l−1 after at least 6 months of follow-up. Complete response was observed in 60.0% (6/10, one excluded) H. pylori eradicated patients vs. 18.2% (2/11) in non-eradicated patients (p = 0.08; OR = 6.75) after 6–9 months of follow-up. Among uninfected patients, only 13.8% (8/58) presented complete response. Two non-treated controls were treated after 6–12 months of follow-up, and PLT response was observed in 61.5% (8/13) of H. pylori eradicated patients, and in 19.0% (11/58) of uninfected patients (p = 0.004). Cytotoxin associated gene A and vacuolating cytotoxin gene A IgG antibodies were present in almost all infected patients. Therefore, the study suggests that H. pylori eradication plays a role in the management of H. pylori infected cITP children and adolescents.